I think I am : Philip K. Dick - Rickels, Laurence A. (University of Minnesota Press, 2010)
"For years, noted writer Laurence A. Rickels often found himself compared to novelist Philip K. Dick--though in fact Rickels had never read any of the science fiction writer's work. When he finally read his first Philip K. Dick novel, while researching for his recent book The Devil Notebooks, it prompted a prolonged immersion in Dick's writing as well as a recognition of Rickels's own long-documented intellectual pursuits. The result of this engagement is I Think I Am: Philip K. Dick, a profound thought experiment that charts the wide relevance of the pulp sci-fi author and paranoid visionary."--Provided by publisher.